Reflections on diversity and citizenship : Bangladesh and beyond - Kāmāla, Mesabāha; Rashid, Mansoora, 1958-; Yasmeen, Shahnaz; Hasan, Zaki, 1977- (Shrabon Prokashani, 2005)
Contributed articles presented earlier at a seminar held in Dhaka, Septemebr, 2005 coordinated by ActionAid Bangladesh, Reflect Development Unit..